2022
DOI: 10.1001/jamanetworkopen.2022.5491
|View full text |Cite
|
Sign up to set email alerts
|

Association of Genetic Variants Linked to Late-Onset Alzheimer Disease With Cognitive Test Performance by Midlife

Abstract: Key Points Question At what age do individuals with higher genetic risk of Alzheimer disease first show cognitive differences from individuals with lower genetic risk, and which of 32 cognitive measures show the earliest difference? Findings In this cross-sectional study of 405 050 individuals, higher genetic risk of Alzheimer disease significantly modified the association of age with 13 of 32 cognitive measures. Best-fitting models suggested that higher ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 67 publications
5
15
0
Order By: Relevance
“…Zimmerman et al examined the age-related genetic effect of APOE and PRS in UKBB. Similar to our findings, they reported that an AD PRS modified the association between age and cognition, that APOE ε4 allele carriers experienced earlier cognitive decline than non-carriers did, and that models using the PRS that excluded APOE ε4 had attenuated and later modification of age associations compared to when APOE was included in the PRS[45]. Our study also demonstrated a pattern in the timing of the earliest detectable genetic effect on rate of change in beta-amyloid (age ~55), tau (age ~65), and cognition (age ~65-70) that aligns with findings from Hanseeuw et al[46].…”
supporting
confidence: 90%
“…Zimmerman et al examined the age-related genetic effect of APOE and PRS in UKBB. Similar to our findings, they reported that an AD PRS modified the association between age and cognition, that APOE ε4 allele carriers experienced earlier cognitive decline than non-carriers did, and that models using the PRS that excluded APOE ε4 had attenuated and later modification of age associations compared to when APOE was included in the PRS[45]. Our study also demonstrated a pattern in the timing of the earliest detectable genetic effect on rate of change in beta-amyloid (age ~55), tau (age ~65), and cognition (age ~65-70) that aligns with findings from Hanseeuw et al[46].…”
supporting
confidence: 90%
“…This also implicates APOE as the main driver of these cognitive differences in the WRAP sample, which has also been reported in other samples 13 . In addition, a recent cross‐sectional analysis of the UK Biobank, 49 which also evaluated the age of cognitive divergence by an AD PRS that included APOE and was composed of similar variants as ours, found in sensitivity analyses that the interaction between the PRS and age was not significant if APOE was taken out of the PRS and included as a separate term in the models. Our results as well as others that use a PRS could fluctuate with the addition of variants to the PRS.…”
Section: Discussionsupporting
confidence: 69%
“…Specifically, we calculated the AD-GRS based on 25 SNPs, each corresponding to a different loci (Table 1) not including the APOE region, identified as genome-wide significant in the 2019 International Genomics of Alzheimer's Project meta-analyzed genome-wide association study on late-onset AD in Europeans. 13 This approach is similar to prior studies 1,2,6 and follows recommendations from prior work that found genetic architecture of late-onset AD is oligogenic (e.g. due to a small set of genes), 14 The AD-GRS was calculated in PLINK as a weighted sum of an individual's AD risk allele count; with weights as the β coefficient for AD for each SNP.…”
Section: Study Populationmentioning
confidence: 99%
“…Recent work in the large UK Biobank suggested the association between higher AD genetic risk and worse cognition may begin in midlife. 6 In a middle-age cohort, several individual AD-risk loci were nominally associated with poor cognition. 7 However, another study found no associations between AD genetic risk or APOE genotype and midlife cognition.…”
mentioning
confidence: 99%
See 1 more Smart Citation